Tradisi Arebbe dalam Masyarakat Situbondo,: Studi Living Hadis - Nabawiyah, Habsatun (Al-Bayan: Jurnal Ilmu al-Qur'an dan Hadist, 2018)
Hadith as the second source of Islamic law is not only interpreted in theological aspect, but also being interpreted as one of social behaviors. So that hadith is often becomes the basic of every social activity in certain community or society. It means that people use hadith as inspiration of their daily activity. This article discusses the islamic society, located at Trebungan, Mangaran, Situbondo, who apply it as the basic of social activity in their village. It is called Arebbe, one of tradition in islamic society that based on hadith. This article uses the Karl Mannheim's sociological science theory, behavior interpretation, to know the interpretation of Trebungan's people about Arebbe. Mannheim classified the behavior's meaning of social action into 3 types: objective meaning, expressive meaning, and documentary meaning.